O sujeito discursivo no gênero artigo científico - Batista, Rodrigo Henrique (2008)
This research aims at analyzing speeches of discursive subject as subjectivity instance in academic-scientific text genre. Considering subject realizes different positions in discursive web, it is hypothesized speeches of a subjectivity instance reveal different voices, constituted from several manifestations of discursive subject. Theoretically, it is taken as support French Discourse Analysis conceptual web, focusing the notions of subject, position-taken, subjectivity instance, enunciative heterogeneities and discursive genres. A paper entitled Uma disputa no contexto brasileiro entre alguns seguidores de um modelo de Análise do Discurso (Linha francesa) e os que usam metodologias de pesquisa interpretativa e/ou quantitativa em Lingüística Aplicada , by John Robert Schimitz, published in a national periodic, was taken as corpus to approach hidden discursive spaces in theoretical positions from Bertoldo (2000) and Coracini (1988) on Applied Linguistics theoretical basis. It was realized in such paper some dislocations in terms of authorship, what configured the following research questions: i) how subjectivity instance of authorship constitutes itself in academic-scientific texts; ii) how such instance constructs a position-taken as scriptor-subject in academic-scientific genre and iii) which voices features such subject-instance, being inscribed in a discursive formation.